2012
DOI: 10.1007/s00464-012-2472-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes after totally robotic sacrocolpopexy for treatment of pelvic organ prolapse

Abstract: Our experience indicates that using the Da-Vinci robotic system is feasible, safe, and effective for the treatment of pelvic organ prolapse with good long-term results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…mesh erosion occurred in 31 of 1417 patients (2%) with specific information available [10,11,[16][17][18][19][20][21][22]25,[27][28][29][30][31][32][33][34][35][38][39][40]. Significant heterogeneity in mesh erosion was found among studies ( p < 0.01), thus suggesting difference in sample size, follow-up, and risk factors.…”
Section: Surgical-related Complicationsmentioning
confidence: 98%
See 4 more Smart Citations
“…mesh erosion occurred in 31 of 1417 patients (2%) with specific information available [10,11,[16][17][18][19][20][21][22]25,[27][28][29][30][31][32][33][34][35][38][39][40]. Significant heterogeneity in mesh erosion was found among studies ( p < 0.01), thus suggesting difference in sample size, follow-up, and risk factors.…”
Section: Surgical-related Complicationsmentioning
confidence: 98%
“…Estimated blood losses were of limited entities; no studies reported a mean or median blood loss >150 ml [10,11,. Most studies reported a hospital stay <2 d [16,31,34,35]; three studies reported a median/mean hospitalization time >3 d [18,30,38]. However, the lack of uniformity in reporting operative parameters and the highly variable kinds of concomitant procedures performed (eg, the addition of concomitant hysterectomy) do not allow us to make a fair comparison between groups and evaluate how different surgical volume and different study periods influenced operative results.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 3 more Smart Citations